A rotatividade docente numa escola da rede estadual de ensino - Silva, Jadilson Lourenço da (2007)
This study investigates the turnover rate of the teachers in the public education system of the State of Sao Paulo. The research field was an Elementary and High School in the city of Franco da Rocha, between 1997 and 2006. The teachers turnover was verified from the fact that teachers from different professional status (permanent, temporary and stable) were not remaining in the same school throughout the year and the subsequent teaching years of the investigated period. The data collection about the stability of the teachers in the schools was done by the analysis of the class logbooks in the years researched. Through semi-structured interviews, it has been verified the perception of the school agents about the influence of the teachers turnover in the organization of school s pedagogic work. The results pointed the existence of a high turnover rate in Sao Paulo, manifested in the different professional categories that compose the state school system. Between 1997 and 2003, the minor turnover was among the stable teachers, who are the minority. In the school researched it was also verified that the permanent teachers the second biggest group of teachers present the largest turnover rate between 1997 and 2006. The temporary teachers the biggest group by the period present the second largest rate. However, this ratio was significantly lower than the permanents. In some years, pointing out that category doesn t have job stability and, at each school year, have to go through a new process of selection to take classes, whose discretion is the time spent in the classroom. These results are the opposite of the common sense, that job stability evokes the permanence. The interviews also revealed school agents perception about public policies that are needed to avoid the harming of teachers work